If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 5 = 2n Reorder the terms: 5 + n = 2n Solving 5 + n = 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 5 + n + -2n = 2n + -2n Combine like terms: n + -2n = -1n 5 + -1n = 2n + -2n Combine like terms: 2n + -2n = 0 5 + -1n = 0 Add '-5' to each side of the equation. 5 + -5 + -1n = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1n = 0 + -5 -1n = 0 + -5 Combine like terms: 0 + -5 = -5 -1n = -5 Divide each side by '-1'. n = 5 Simplifying n = 5
| 5k-3=3+2k | | 3x-10=6x-19 | | 2y^2+4y-48=0 | | 6x=12+x | | -6(n+2)+15=-3n-12 | | 57-2x=34x+17 | | 2/4+x=15 | | -4+2k=k-3 | | 42x-6y=24 | | 6x-36+8=8x-12 | | -122-8x=71-43x | | -1+2m=m+3 | | 5n^2=-30n | | (x+2)(x^2-7x+4)= | | 2x+9=37-9 | | (7x^2+9x+7)(9x-4)= | | (X-4)(x-3)=1056 | | a-5/7+2a-3/5 | | (4x^3+2x^2+3x+4)(4x+4)= | | 4+2n-3=8n+17-4n | | 30-6m=-6(3m+7) | | 24v^3-9v^2/3v^2 | | (4-x^2)(1+x)=0 | | 2(a-4)=3 | | (x-7)(x^2+3x-3)= | | 3x^(4/5)=48 | | 35/p=3 | | ax^2-x+c=0 | | -2x-8y=14 | | m-12=2 | | m/3.5=4 | | (x^2-6x^2+11x-6)/(x^3-9x^2+26x-24) |